Social Campaign Media Design of Books for Papua - Oktavian Eka Wahyuning Tyas; Didit Widiatmoko Soewardikoen (Wimba : Jurnal Komunikasi Visual, 2015)
Education facilities in Papua is insufficient, so the amount of illeteracy is still high in that region. Later, there is a community that named as "@bukuntukpapua", an independent movement which cares about the education issues in Papua. The main purpose of that community is collecting books and donation, that will be managed into a small library in Papua. Those efforts are hoped to improve the education of people in Papua, especially for the children in early age. Reading and writing are one of the efforts to decrease the illeteracy in Papua. Unfortunately, "@bukuntukpapua" doesn't have the actual visual medias for its activities. This problem causes only a few people who know about this movement. In order to solve that problem, the design of promotion medias for this social campaign program should be made. Various data was obtained through observation, interviews, research from the books, and also by spreading the questionnaires to any respondent who are representative for the target audience. The results from that analysis showed customers' will for the social campaign media. By the results of that, the concept of social campaign media is persuading people to get involve in this campaign. The medias which will be used are website, social media, infographic, brochure, poster, digital poster, book drop box, packaging box, and merchandise. Hopefully this design will help "@bukuntukpapua" in implementation of the social campaign, so people will know about this program and participate to make it success.